Identification and study of the spectrum of the periodic traffic - Ігнатов, В. О.; Ладигіна, О. А. (Problems of Informatization and Control, 2015)
The algorithm and the method of determining the structure and the optimization of the parameterestimates periodic traffic developed. The task of verifying the optimal model structure and parametersof multicomponent periodic traffic to background interference solved. Experiment optimal estimationof periodic traffic with the first three harmonics done